Reliability of point-of-care shoulder ultrasound measurements for subacromial impingement in asymptomatic participants - Yuan, Xiaoning; Lowder, Ryan; Aviles-Wetherell, Kathelynn; Skroce, Christian; Yao, Katherine V.; Soo Hoo, Jennifer (Frontiers in Rehabilitation Sciences, 2022)
Background: Rehabilitation is the key to management of patients with subacromial impingement syndrome to prevent disability and loss of function. While point-of-care musculoskeletal ultrasound aids clinical diagnosis of subacromial impingement syndrome, many patients do not demonstrate the classic findings of dynamic supraspinatus tendon impingement beneath the acromion on ultrasound. The objective of this study was to establish the most reliable shoulder ultrasound measurements for subacromial impingement, by evaluating the intra-rater and inter-rater reliability of measurements in asymptomatic participants. Methods: Eighteen participants (9 women, 9 men, mean ± standard deviation: 34.6 ± 7.9 years of age) underwent bilateral shoulder ultrasound evaluations with measurements for subacromial impingement (acromiohumeral distance, acromion-greater tuberosity distance, supraspinatus tendon, subacromial-subdeltoid bursa, and subacromial-subdeltoid bursal fluid thickness) performed by two sports medicine physicians. Intra-class coefficients were calculated to determine the intra- and inter-rater reliability of shoulder ultrasound images and measurements. Results: Intra-rater reliability for acromiohumeral distance (0.76-0.79), supraspinatus tendon (0.91-0.95), subacromial-subdeltoid bursa (0.76-0.84), and subacromial-subdeltoid bursal fluid thickness (0.75-0.81) was found to be good to excellent, whereas inter-rater reliability ranged from poor to moderate. Conclusions: Acromiohumeral distance in neutral position and short axis ultrasound measurements of supraspinatus tendon, subacromial-subdeltoid bursa, and subacromial-subdeltoid bursal fluid thickness in the modified Crass position were the most reliable for subacromial impingement in asymptomatic participants. We recommend validation of these measurements in a symptomatic population to aid diagnosis and direct rehabilitation of patients with suspected subacromial impingement, and to increase point-of-care ultrasound uptake, availability, and training among rehabilitation professionals across health systems.